Australia's aborigines [videorecording] - Breeden, Stanley; Kane, Dennis B.; Skinner, Thomas; Wright, Belinda; National Geographic Society, Washington, D.C.; WQED (Television station : Pittsburg, Pa.). ([Washington, D.C.] The Society, 1988)
Portrays the surviving Gagudju aborigines in Northern Australia. Describes the history, tribal groups, social life and customs.
VHS.
Narrated by Richard Kiley ; edited by Barry Nye.
Keywords: Australian aborigines